Islam and English law : rights, responsibilities, and the place of Shari'a - Griffith-Jones, Robin (Cambridge : Cambridge University Press, 2013)
'Former Archbishop of Canterbury Rowan Williams triggered a storm of protest when he suggested that some accommodation between British law and Islam's shari'a law was'inevitable'. His foundational lecture introduced a series of public discussions on Islam and English Law at the Royal Courts of Justice and the Temple Church in London. This volume combines developed versions of these discussions with new contributions.'--
Preface / Robin Griffith-Jones -- Introduction / Stephen Hockman -- Part I. The Archbishop of Canterbury and Shari'a Law: 1. The'unavoidable' adoption of shari'a law?: the generation of a media storm / Robin Griffith-Jones; 2. Civil and religious law in England: a religious perspective / Rowan Williams -- Part II. The Archbishop's Proposal for'Transformative Accommodation': Sharia and secular democracy: is Islamic law compatible with the European Convention on Human Rights?; 3. The Refah case at the European Court of Human Rights / Nicolas Bratza; 4. The compatibility of an Islamic/shari'a law system or shari'a rules with the European Convention on Human Rights / Dominic McGoldrick; 5. An analysis of the relationship between shari'a and secular democracy and the compatibility of Islamic law with the European Convention on Human Rights / Mashood A. Baderin; 6. Dignity and religion / Christopher McCrudden; Legal Pluralism: Should English Law Give Greater Recognition to Islamic Law?: 7. Family law: current conflicts and their resolution / Elizabeth Butler-Sloss and Mark Hill; 8. Islamic finance, alternative dispute resolution and family law: developments towards legal pluralism? / Ian Edge; 9. Judging Muslims / Prakash Shah; 10. From Muslim migrants to Muslim citizens / Shaheen Sardar-Ali; 11. Ontario's'shari'a court': law and politics intertwined / Marion Boyd; Accommodation or Conflict: Trajectories in the United Kingdom: 12. Religious rights and the public interest / Robin Griffith-Jones -- Part III. Responsibilities and Rights: Freedom of Speech, Incitement to Religious Hatred: Beyond the Divide?: 13. Where to draw the line, and how to draw it / Sydney Kentridge, A note: the Satanic Verses and the Danish cartoons / Robin Griffith-Jones; 14. Censor or censure: maintaining civility / Tariq Modood; 15. In praise of'fuzzy law' / Albie Sachs; Religion, the state and meaning of'jihad': 16. Towards an Islamic society, not an Islamic state / Abdullahi An-Na'im; 17. Following shari'a in the West / Tariq Ramadan; 18. Violence, personal commitment and democracy / Khaled Abou El Fadl -- Part IV. Prospect: Equality before God and before the Law: 19. Equal before God / David F. Ford; 20. Equal before the law / Nicholas Phillips.
Includes bibliographical references (p. 294-305) and index.
Keywords: Religion and law -- United Kingdom; Islamic law -- United Kingdom; Conflict of laws -- United Kingdom; Conflict of laws (Islamic law) -- United Kingdom; Islamic law -- Europe; Religion and law -- Europe; Conflict of laws -- Europe